2013
DOI: 10.1093/brain/awt132
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the electroencephalogram and sleep phenotype in the R6/2 mouse model of Huntington’s disease

Abstract: Deficits in sleep and circadian organization have been identified as common early features in patients with Huntington's disease that correlate with symptom severity and may be instrumental in disease progression. Studies in Huntington's disease gene carriers suggest that alterations in the electroencephalogram may reflect underlying neuronal dysfunction that is present in the premanifest stage. We conducted a longitudinal characterization of sleep/wake and electroencephalographic activity in the R6/2 mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
90
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 57 publications
17
90
0
Order By: Relevance
“…This suggests that even in the presence of sufficient sleep duration, the restorative effects may be compromised during the premanifest stage. These results of fragmented sleep are in line with a recent paper showing major sleep disturbances in manifest HD patients that were also characterized by increased arousals and awakenings55 and data from transgenic animal models of HD showing that sleep quality as well as oscillatory brain activity (EEG) and circadian rhythmicity becomes gradually more disrupted as the disease progresses 11, 12, 14. Furthermore, it has recently been shown that resting EEG alterations in pre‐HD individuals may be related to the course of the pathological process and to HD endophenotype 43.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This suggests that even in the presence of sufficient sleep duration, the restorative effects may be compromised during the premanifest stage. These results of fragmented sleep are in line with a recent paper showing major sleep disturbances in manifest HD patients that were also characterized by increased arousals and awakenings55 and data from transgenic animal models of HD showing that sleep quality as well as oscillatory brain activity (EEG) and circadian rhythmicity becomes gradually more disrupted as the disease progresses 11, 12, 14. Furthermore, it has recently been shown that resting EEG alterations in pre‐HD individuals may be related to the course of the pathological process and to HD endophenotype 43.…”
Section: Discussionsupporting
confidence: 90%
“…Our study therefore is the first qEEG study performed during sleep in premanifest and manifest patients with HD and indicates alterations in the NREM‐ and particularly the REM‐dependent oscillatory activity of the brain associated with disease burden in gene carriers. Some of our findings such as the decrease in the 3 to 8Hz range and the increase in the high‐frequency (32–36Hz) range in the early HD group are somewhat similar to findings in transgenic animal studies reporting a progressive decrease in low‐frequency (delta) and increase in high‐frequency (beta–gamma) activity in sleep 11, 12, 58. The REM‐dependent increase in the 1 to 2Hz range is unexpected and could be related to increased REM intensity (density of REM), a hypothesis that remains to be tested.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results obtained in baseline recordings using abdominally placed telemeters were discordant from those previously published in the same strain (19). Consequently, we replicated our study of nNOS KO and WT mice using tethered EEG and electromyographic (EMG) recordings, which more closely approximated the previously published procedures and which we have also used previously in both rats (20) and mice (21). Because the results from these two types of recordings in our laboratory were largely coincident (compare Fig.…”
Section: Activation Of Cortical Nnos Neurons Is Related To Nrem Sleepsupporting
confidence: 79%